Maternal and Perinatal Outcomes in Women Planning Vaginal Birth After Cesarean (VBAC) at Home in England: Secondary Analysis of the Birthplace National Prospective Cohort Study. Issue 2 (June 2017) - Rowe, R.; Li, Y.; Knight, M.; Brocklehurst, P.; Hollowell, J.
Abstract : ( BJOG . 2016;123:1123–1132) Some women in England who have undergone a cesarean section (CS) in an earlier pregnancy prefer a planned vaginal birth after cesarean (VBAC) in a midwifery-led setting, such as at home, in a freestanding midwifery unit, or in an alongside midwifery unit which resides in the same facility as a hospital obstetric unit (OU). However, present national guidelines suggest that women with a previous CS plan subsequent births in an OU to avoid maternal and fetal complications. This study aimed to compare vaginal birth rates in women planning VBAC at home to those planning VBAC in an OU, and to determine transfer rates for those planning VBAC at home. In addition, analysis of maternal and perinatal outcomes for these groups was undertaken.